Gut microbiome differences between amyotrophic lateral sclerosis patients and spouse controls. Issue 1 (2nd January 2022) - Hertzberg, Vicki S.; Singh, Harinder; Fournier, Christina N.; Moustafa, Ahmed; Polak, Meraida; Kuelbs, Claire A.; Torralba, Manolito G.; Tansey, Malú G.; Nelson, Karen E.; Glass, Jonathan D.
Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that is incurable and ultimately fatal. Few therapeutic options are available to patients. In this study, we explored differences in microbiome composition associated with ALS. Methods: We compared the gut microbiome and inflammatory marker profiles of ALS patients (n = 10) to those of their spouses (n = 10). Gut microbiome profiles were determined by 16S rRNA gene sequencing. Results: The gut microbial communities of the ALS patients were more diverse and were deficient in Prevotella spp. compared with those of their spouses. In contrast, healthy couples (n = 10 couples of the opposite sex) recruited from the same geographic region as the patient population did not exhibit these differences. Stool and plasma inflammatory markers were similar between ALS patients and their spouses. Predictive analysis of microbial enzymes revealed that ALS patients had decreased activity in several metabolic pathways, including carbon metabolism, butyrate metabolism, and systems involving histidine kinase and response regulators. Conclusions: ALS patients exhibit differences in their gut microbial communities compared with spouse controls. Our findings suggest that modifying the gut microbiome, such as via amelioration of Prevotella spp. deficiency, and/or altering butyrate metabolism may have translational value for ALS treatment.